2018
DOI: 10.1002/2017gl076600
|View full text |Cite
|
Sign up to set email alerts
|

Wettability and Flow Rate Impacts on Immiscible Displacement: A Theoretical Model

Abstract: When a more viscous fluid displaces a less viscous one in porous media, viscous pressure drop stabilizes the displacement front against capillary pressure fluctuation. For this favorable viscous ratio conditions, previous studies focused on the front instability under slow flow conditions but did not address competing effects of wettability and flow rate. Here we study how this competition controls displacement patterns. We propose a theoretical model that describes the crossover from fingering to stable flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
77
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 48 publications
8
77
1
Order By: Relevance
“…1). Generally, stronger fingering and larger trapped area of defending fluid are observed when the medium becomes more disordered (increasing I v ) and more hydrophobic (increasing θ ), implying a less efficient displacement, consistent with previous observations [9][10][11][12][19][20][21]23,52]. Figure 3 also demonstrates the "competition" between the destabilizing effect due to uneven distribution of capillary resistance and stabilizing effect from cooperative pore filling events, which have a higher occurrence when contact angle is small.…”
Section: Resultssupporting
confidence: 88%
“…1). Generally, stronger fingering and larger trapped area of defending fluid are observed when the medium becomes more disordered (increasing I v ) and more hydrophobic (increasing θ ), implying a less efficient displacement, consistent with previous observations [9][10][11][12][19][20][21]23,52]. Figure 3 also demonstrates the "competition" between the destabilizing effect due to uneven distribution of capillary resistance and stabilizing effect from cooperative pore filling events, which have a higher occurrence when contact angle is small.…”
Section: Resultssupporting
confidence: 88%
“…Such transition from capillary to capillary‐viscous regimes occurs when the distance from injection wells decreases during water flooding in EOR (Arshadi et al, ; Rücker et al, ) and further identifies different pore‐scale mechanisms of fluid‐fluid interface advancements (Krevor et al, ). In capillary imbibition, studies on pore‐scale events, including Haines jump (Haines, ), corner flow (Dong & Chatzis, ), and snap off (Roof, ), have shown that the pore‐scale mechanisms not only impact the displacement patterns and efficiency (Chen, Guo, et al, ; Hu et al, ; Odier et al, ) but also contribute to the macroscopic hydraulic properties at the Darcy scale (Niessner et al, ). For capillary‐viscous regime in imbibition, these local displacement events would be suppressed as viscous forces increasingly dominate the displacement processes (Odier et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the pattern for the strong drainage condition (Figure ), we see that generally, the invading phase is more compact in the weak drainage case. This behavior is due to the interface‐smoothening effect of the in‐plane curvature (Glass et al, ; Yang et al, ), which is analogous to the stabilization effect due to cooperative filling in porous media (Holtzman & Segre, ; Hu, Wan, et al, ; Trojer et al, ). In fact, the simulated patterns with the strong viscosity contrast ( M = 0.005) for both the strong and weak drainage cases qualitatively resemble those observed in the experiment by Trojer et al () where M = 0.003.…”
Section: Resultsmentioning
confidence: 99%